Kedudukan Visum Et Repertum Dalam Dakwaan Penuntut Umum Terhadap Tindak Pidana Penganiayaan - Saleky, Dewa Daniel Andreas; Rado, Rudini Hasyim; Badilla, Nurul Widhanita Y. (Universitas Musamus, 2024)
This study aims to determine the role of visum et report in preparing the public prosecutor's indictment and to determine the evidentiary power of visum et report as evidence in the case of persecution crime. To support this research, the author uses empirical juridical methods with data obtained through primary and secondary sources; then, the data is analyzed descriptively and qualitatively. From the results of the research conducted, it can be seen that the visum et repertum has a vital role in providing a clear picture of the injuries suffered by the victim by matching the results of the visum et repertum with existing witness testimony. It also plays a role in determining the alleged article to fulfill the criminal elements of the defendant's actions to facilitate the prosecutor in preparing the indictment. The evidentiary power of the visum et repertum as valid evidence in the case of the crime of assault has the same high evidentiary power as other evidence that is also submitted by the public prosecutor in the trial because it refers to the provisions of the criminal procedure law, besides that the visum et repertum does not have binding and non- compelling power for the judge.